Identification of Factors: Affecting the Performance of the Sri Lanka Netball Team - Wanasingha, Sanjeevani; Senaweera, Lalith Nimal (Advances in Social Sciences Research Journal, 2023)
This study employs a critical examination and methodical analysis of factors affecting the performance of the National netball team performance of Sri Lanka. Accordingly, the document will focus on (a) Identifying the factors affecting the performance of the national Netball team. (b) Reveal the relationships between the above-identified factors vs the performances of the team. (c) Identify the insights on how those findings are applied in the refereeing era. (d) Derive conclusions and recommendations of research findings for performance enhancement of the National Netball team. The findings of this document will emphasize National level Netballers in Sri Lanka to achieve their pinnacles in individual and team performances in order to keep the National flag high in the international netball arena. Further, these findings can be applied to other team sports and team-based professional environments for enhancing their performances too. Also, the author indirectly expects those revealed findings will simultaneously affect the promotion of the game and uplift women’s empowerment among 52% of the feminine population in Sri Lanka, for their wellbeing.